Flow cytometric analysis of human dental pulp tissue - Mangkornkarn, C; Steiner, J C; Bohman, R; Lindemann, R A (Journal of endodontics, 1991)
Existing knowledge regarding the cellular components of the dental pulp has been derived primarily from classical methods of histology and biochemistry. Since observations made from prepared tissue sections are static, it is not clear whether this accurately reflects the cellular dynamics of living pulp tissue. Therefore, we developed a method to analyze vital human pulpal tissue by flow cytometry. To test this method, two analyses of the prepared pulpal tissue were performed. First, the prepared tissue was stained with monoclonal antibodies to detect lymphocyte subpopulations. Second, the tissue was processed for DNA analysis of individual cells. Results demonstrated that lymphocytes bearing CD4 and CD8 antigens were clearly detected in pulpal tissue by this method. No B cells were found in any sample. DNA analysis revealed two distinct cell populations. Approximately 88% were small and 12% were large. According to DNA content, 90% of all cells were noncycling and 10% were cycling. These results demonstrate the feasibility of using flow cytometric analysis to examine, at a quantitative level, the cellular heterogeneity of the human dental pulp.